Pengaruh Beban Kerja dan Kompensasi Terhadap Kinerja Karyawan Grand Cemara Hotel Jakarta - Febriyanti, Andini; Edison, Emron (Manajemen dan Pariwisata, 2024)
This research was conducted at Grand Cemara Hotel Jakarta. The study aims to evaluate "The Effect of Workload and Compensation on Employee Performance of Grand Cemara Hotel Central Jakarta" using descriptive and verification quantitative analysis methods with multiple linear regression approaches. The independent variables in this study are Workload and Compensation, while the dependent variable is Employee Performance. The number of samples used was 52. This study aims to identify the impact of independent variables on the dependent variable. The results of the validity and reliability of the questionnaire show that all questionnaire statements are reliable and valid. Descriptively, Workload is rated "Fair", as well as Compensation and Employee Performance. The verification analysis results show that Workload and Compensation have a positive and significant effect on Employee Performance partially. Together, both have a positive and significant effect. The coefficient of determination or R2 reaches 98.70%, while the remaining 1.30% is influenced by other variables not included in the scope of this study.